A bacteriophage cocktail can efficiently reduce five important Salmonella serotypes both on chicken skin and stainless steel - Gvaladze, Tamar; Lehnherr, Hansjörg; Hertwig, Stefan (Frontiers in Microbiology, 2024)
Salmonella is one of the most important zoonotic pathogens and is mostly transmitted through food of animal origin. Application of bacteriophages is a promising tool to biocontrol Salmonella on both food and food contact surfaces. In this study, we evaluated the effectiveness of a 6-phage cocktail for the reduction of S. Enteritidis and a mixture of 5 major Salmonella serotypes (S. Enteritidis, S. Typhimurium, S. Infantis, S. Paratyphi B and S. Indiana) on chicken skin and stainless steel. A phage cocktail with a final concentration of 10 7 PFU/cm 2 was sprayed on these surfaces. After adding the phage cocktail, the samples were incubated at RT (approx. 23 °C) for different periods of time. The phage cocktail caused a significant reduction of S. Enteritidis and the mixed culture on chicken skin 30 min after phage addition, with 1.8 log10 and 1 log10 units, respectively. Reduction rates (1.2-1.7 log10 units) on stainless steel after 30 min were similar. Four hours after addition, the phage cocktail caused a significant reduction on both surfaces up to 3 log10 units on chicken skin and 2.4 log10 units on stainless steel. In a further experiment, bacteria added to stainless steel were not allowed to dry to simulate a fresh bacterial contamination. In this case, the bacterial count of S. Enteritidis was reduced below the detection limit after 2 hours. The results demonstrate that this phage cocktail has potential to be used in post-harvest applications to control Salmonella contaminations.